Protection of cultural heritage from earthquakes : The NIKER project and the related research at UMinho - Oliveira, Daniel V. (2014)
The European Commission has recently funded a major research project (NIKER) which aimed at developing an integrated methodology for the systemic improvement of the seismic behaviour of cultural heritage assets. This paper provides an overview of the project and presents the most relevant contributions from University of Minho as partner of the project